Low pretreatment lymphocyte/monocyte ratio is associated with the better efficacy of neoadjuvant chemotherapy in breast cancer patients. Issue 2 (1st February 2020) - Peng, Yang; Chen, Rui; Qu, Fanli; Ye, Ying; Fu, Yong; Tang, Zhenrong; Wang, Yihua; Zong, Beige; Yu, Haochen; Luo, Feng; Liu, Shengchun
ABSTRACT: The combination of some parameters, including the neutrophil to lymphocyte ratio (NLR), platelet to lymphocyte ratio (PLR), lymphocyte to monocyte ratio (LMR) and neutrophil to monocyte ratio (NMR), which are associated with patient prognosis, our goal is to find the best indicator to predict the efficacy of neoadjuvant chemotherapy（NAC）in breast cancer patients. A cohort of 808 breast cancer patients treated with NAC and subsequent surgery was analyzed retrospectively. In addition, 2424 people without breast cancer served as the normal group, which included three-fold more individuals compared with the breast cancer group. Receiver operating characteristics (ROC) curves were used to determine the optimal cutoff values of inflammatory markers and compare their predictive capacity. No significant differences in age, PLR, LMR and NMR were noted between the normal group and the patient group. However, the mean value of the NLR was significantly increased in breast cancer patients (2.28) compared with the normal population (2.04) ( P < .05). The LMR was significantly associated with age ( P = .003), menopausal status ( P = .004), cT category ( P = .017), cN category ( P = .024) and response to NAC ( P = .001). The multivariate analysis indicated that among these inflammatory markers, the LMR (6.1 < vs ≥ 6.1) was the only independent predictive factor for the efficacy of NAC (OR = 1.771, 95% CI = 1.273–2.464, P = .001). A low LMR is considered a favorable predicative factor of the efficacy of NAC in breast cancer patients.